2021
DOI: 10.1002/iid3.449
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of Syk gene methylation in colorectal cancer

Abstract: Background: Metastasis of colorectal cancer (CRC) extremely affects the prognosis of CRC patients. Recently, the genetic methylation has been shown to associate with tumor metastasis. This research aimed to explore the Syk gene, which is frequently hypermethylated in different cancers, and its impact on the metastasis of CRC cells. Methods: We employed the UALCAN database for the detection of the methylation levels of Syk in different cancers. CIBERSORT, TIMER and TISIDB tools were employed to analyze the ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…We further explored the relationship between tumor-infiltrating immune cells and the risk score with seven common acceptable methods of estimating the infiltrating immune cells, including TIMER (Bu F, 2021), CIBERSORT ( Bu et al, 2021 ), xCell ( Oshi et al, 2021 ), quanTIseq ( Finotello et al, 2019 ), MCPcounter ( Li et al, 2021 ), EPIC ( Zeng et al, 2021 ), and CIBERSORT-ABS ( Tamminga et al, 2020 ). The synthetical analysis showed that the risk score was more positively related to tumor-infiltrating immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…We further explored the relationship between tumor-infiltrating immune cells and the risk score with seven common acceptable methods of estimating the infiltrating immune cells, including TIMER (Bu F, 2021), CIBERSORT ( Bu et al, 2021 ), xCell ( Oshi et al, 2021 ), quanTIseq ( Finotello et al, 2019 ), MCPcounter ( Li et al, 2021 ), EPIC ( Zeng et al, 2021 ), and CIBERSORT-ABS ( Tamminga et al, 2020 ). The synthetical analysis showed that the risk score was more positively related to tumor-infiltrating immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…A lower SYK protein expression and methylation are also connected with the metastasis of other cancer, including lung cancer, liver cancer, oral squamous cell cancer, pancreatic cancer, bladder cancer, gastric cancer, and urinary cancer [ 7 , 8 , 9 ]. Here, colorectal cancer (CRC) is also associated with this gene, and the loss of its expression is found in several CRC tissues [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%